Identifikasi Tumbuhan Tingkat Rendah Yang Dimanfaatkan Sebagai Tumbuhan Obat-obatan - Syarifah Widya Ulfa; Riza Nazila Azri; Alimatusakdia Panggabean; Audia Fadilla (CV. ITTC INDONESIA, 2024)
The purpose of this study is to identify lower plants that have medicinal uses. Descriptive research, which seeks to provide an objective description of events and occurrences, was the research approach employed in this study. According to study findings, lower plants have antibacterial, anti-inflammatory, anticancer, wound-healing, and other medical effects. They can also be used to treat digestive, pulmonary, and cardiovascular issues as well as preserve bone and tooth health. Because lower plants are abundant in bioactive substances that are good for human health, they may be exploited as a source of alternative natural medicine. But more investigation is required to support its efficacy claims.